Carcass Characteristic of Indigenous Chicken Fed on Diets Containing German Cockroach (Blattela germanica) Meal in Kenya - V. M. , Ngaira; F. O. , Wayua; R. O. , Mosi; C. C. , Wambui; P. A. O. , Alaru; V. O. , Ochieng; E. D., Ilatsia (African Journal of Education,Science and Technology (AJEST), 2026)
Edible insects are available for use in insect-based-feed, however there is limited information on carcass characteristics and sensory tests of chicken fed on German cockroaches (Blattela germanica). This study assessed the effects of replacing fishmeal (FM) with varying levels of processed B. germanica meal (BGM). Seventy-two grower chicken of eight weeks old, comprising an equal number of males and females, were used as sampling units in a completely randomized design (CRD). Four treatments were replicated three times and fed ad lib on different diets for period of fifty-six days. The treatments were isocaloric and isonitrogenous and comprised of - diet TA (3.5 %FM, 0.5% PBGM), TB (2.5 %FM, 1.5% PBGM), TC (2 % FM, 2% PBGM), and TD (4 %FM, 0% FM). Four birds per treatment were sacrificed on day 112. The birds were slaughtered, dressed, and dissected into prime cuts (thighs, drumstick, breast, wings) that were weighed and expressed as a percentage of live birds. Samples of breast were cooked and served to a panellist for an organoleptic test. Data were subjected to a one-way analysis of variance for a CRD where samples were treatments while panellists were replicates in SPSS. Weights of plucked bird, dressed bird, thighs, drumstick, and wings of chicken fed on TA, TB, and TC was not significantly different from those feds on the control diet (TD). Similarly, the average percentage of the dressed carcass (65%) and other prime cuts was not different from the control. The flavour, smell, taste, colour, and overall acceptability of breast samples were not significantly different, with a mean score of 4.0 rated as good. The study revealed that replacing up to 50% of fishmeal with BGM does not affect meat quality, meat sensory attributes, and consumers’ acceptability thus actors in the chicken value chain should embrace use of German cockroaches as a protein feedstuff.